2019
DOI: 10.1021/acsearthspacechem.9b00257
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Tropospheric Microhydration Processes of Iodous Acid HOIO

Abstract: The microhydration of iodous acid has been theoretically studied using the ωB97X-D/aug-cc-pVTZ level of theory. Two hydration processes have been examined considering the addition of either successive water molecules or water clusters with a number of water molecules from 1 to 4. The singlet potential energy surface exploration revealed four monohydrates, seven dihydrates, nine trihydrates, and ten tetrahydrates. The thermodynamic properties of the hydration reactions have been calculated at different levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…Optimized geometric parameters and vibrational frequencies for H 2 O at the ωB97X-D/aug-cc-pVTZ level have been already presented in previous studies. The BrHgO geometry was previously computed by Balabanov et al, at CCSD­(T)/CBS, and our geometry compares well with their results. For HOHg, our HgO bond length is also longer (by 0.038 Å) than that computed by Dibble et al, at the CCSD­(T,full)/AwCVTZ level.…”
Section: Discussionsupporting
confidence: 70%
“…Optimized geometric parameters and vibrational frequencies for H 2 O at the ωB97X-D/aug-cc-pVTZ level have been already presented in previous studies. The BrHgO geometry was previously computed by Balabanov et al, at CCSD­(T)/CBS, and our geometry compares well with their results. For HOHg, our HgO bond length is also longer (by 0.038 Å) than that computed by Dibble et al, at the CCSD­(T,full)/AwCVTZ level.…”
Section: Discussionsupporting
confidence: 70%
“…The final level of theory is denoted as CCSD­(T)/CBS + ΔCV + ΔSO + ΔPP + ΔZPE. We have applied this approach previously in a series of papers on atmospheric reactivity of halo-hydrocarbons and a similar approach in previous work on mercury compounds . The counterpoise correction for the estimation of the basis set superposition error was not taken into account because several previous works showed that it could lead to discrepancies in the energetic results. …”
Section: Computational Methodsmentioning
confidence: 99%
“…However, there is an additional release peak between ≈200-350°C, which has been reproduced in another test, hinting at a different re-vaporization process, probably linked to the nature of the deposit in this temperature range (720-620°C). This new release mechanism may be owed to the CsI deposition temperature which resulted in a non-uniform amorphous like layer of deposits (see section 4.1) which is quite different to aerosol impaction [29] so that one can expect strong evolution at the molecular level too (for instance in the structure of the CsI outermost surface), inducing differences in the reaction mechanism -as will be seen with the DFT calculations (section 5).…”
Section: Influence Of Csi Deposition Process: High-temperature (Condi...mentioning
confidence: 99%
“…[28]. Based on all these studies, it is possible to estimate the concentrations of some iodine and caesium species in the gas phase depending on the experimental conditions [29].…”
Section: Introductionmentioning
confidence: 99%